City and nature relationship - resilience through contemporary urban-architectural projects - Andrade, Camila Cesario Pereira de; Castells, Alicia Norma González de (National Journal of City Management, 2023)
The aim of this paper is to enunciate convergences between the contemporary city, the urban-architectural projects and their relationship with nature. Starting from the assumption that the city is an integrating portion of the natural environment, as a complex and uninterrupted system of biotic and abiotic changes, influenced mainly by the culture, values, customs and habits of its residents. To propose based on the project the green infrastructure system, as it enables a better quality of life, the reduction of social and economic asymmetries arising from the environmental context of certain social groups may constitute an alternative to mitigate the degradation of the urban landscape, in addition to providing environmental services essential to the cities’ sustainability.